Identification of VKORC1 interaction partners by split-ubiquitin system and coimmunoprecipitation - Schaafhausen, Anne; Rost, Simone; Oldenburg, Johannes; Müller, Clemens R. (Thrombosis and Haemostasis, 2011)
Since the discovery of vitamin K epoxide reductase complex subunit 1 (VKORC1), the key enzyme for the regeneration of vitamin KH2, numerous studies have addressed the role of VKORC1 in the posttranslational modification of vitamin K-dependent proteins. VKORC1 is also the target protein of anticoagulant drugs of the coumarin type (e.g. warfarin). Genetic variants in VKORC1 have recently been shown to significantly affect the coumarin dose and international normalised ratio level. In the present study, we have used the split-ubiquitin yeast two-hybrid system to identify potential interaction partners of VKORC1. With this system we could identify 90 candidates. Out of these, we focused on VKORC1 itself, its paralog VKORC1L1, emopamil binding protein (EBP) and stress-associated endoplasmic reticulum protein 1 (SERP1). By coimmunprecipitation and colocalisation experiments, we were able to demonstrate evidence for the interaction of these proteins. Mutations in the EBP gene cause X-linked dominant chondrodysplasia punctata (CDPX2) which can be considered as a phenocopy of warfarin embryo-pathy. The interaction could be a link between these phenotypes. SERP1 represents an oxidative stress-associated endoplasmatic reticulum protein with chaperon-like functions. Antioxidant capacities have been described for vitamin K hydroquinone, the substrate of VKORC1. Both VKORC1 and SERP1, might have a synergistic function in eliminating reactive oxygen species generated during the VKOR redox process. Further studies are needed to investigate the role of these proteins in the vitamin K pathway.
Keywords: VKOR; EBP; chondrodysplasia punctata; warfarin embryopathy; SERP1